2023
DOI: 10.1002/cbic.202200794
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked Aggregates of Fusion Enzymes in Microaqueous Organic Media

Abstract: Baeyer-Villiger monooxygenases (BVMOs) are attractive for selectively oxidizing various ketones using oxygen into valuable esters and lactones. However, the application of BVMOs is restrained by cofactor dependency and enzyme instability combined with water-related downsides such as low substrate loading, low oxygen capacity, and water-induced side reactions. Herein, we described a redox-neutral linear cascade with in-situ cofactor regeneration catalyzed by fused alcohol dehydrogenase and cyclohexanone monooxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Regarding the substrate concentration (Figure c), a lower concentration leads to a higher reaction rate, as expected, since it is well-known that most of the BVMO enzymes suffer from substrate inhibition. , High yields were obtained for the reactions with 30, 60, and 125 mM CHL, resulting in 23, 48, and 99 mM ECL with 77, 80, and 79% yields, respectively, revealing 60 mM as the best one. For the higher concentrations, the yields drop significantly to 40% (100 mM ECL) and 13% (63 mM ECL) when using 250 and 500 mM CHL.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Regarding the substrate concentration (Figure c), a lower concentration leads to a higher reaction rate, as expected, since it is well-known that most of the BVMO enzymes suffer from substrate inhibition. , High yields were obtained for the reactions with 30, 60, and 125 mM CHL, resulting in 23, 48, and 99 mM ECL with 77, 80, and 79% yields, respectively, revealing 60 mM as the best one. For the higher concentrations, the yields drop significantly to 40% (100 mM ECL) and 13% (63 mM ECL) when using 250 and 500 mM CHL.…”
Section: Resultssupporting
confidence: 77%
“…The coimmobilization of single enzymes is not considered due to an uncontrollable competitive immobilization. For the linear cascade, the previous study by the authors reported the optimal reaction conditions regarding substrate and cofactor concentrations, and temperature, which was further used in this work. Since the oxidation of CHO by CHMO is the rate-limiting step of the linear cascade, all reactions were performed with the same units of Tm CHMO .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell lysates were harvested, washed, and lysed using RIPA buffer and then centrifuged at 13,000 rpm for 45 min at 4°C ( Vernet et al, 2023 ). The protein concentration was determined using the BCA Protein Assay Kit and diluted in loading buffer (4X).…”
Section: Methodsmentioning
confidence: 99%